Linking Urban Public Spaces and Cultural Institutions to Quality of Life - Krasniqi, Anitë; Hasukic, Amir; Jashari, Elmedina; Chabko, Julita; Kamenská, Natálie (Quality of Life in a Changing World: Spatial, Social and Environmental Perspectives from Maribor and Beyond, 2026)
This study examines four public squares in Maribor—Grajski trg, Trg Generala Maistra, Trg Leona Štuklja, and Židovski trg—across seven dimensions: physical structure, aesthetics, functionality, comfort and safety, utilisation, atmosphere, and accessibility. Results suggest that Grajski trg and Židovski trg carry historical value and symbolic meanings, yet their infrastructure and safety features could be improved. Trg Generala Maistra is a transitional area of social and symbolic significance, but it lacks vibrancy, while Trg Leona Štuklja is the most socially inclusive and dynamic square. The findings highlight that public space quality is not merely a physical design function but also a function of social use and subjective perception. Combining cultural institutions with city squares helps activate the spaces and make them more responsive to citizens. This approach to addressing the quality of urban spaces contributes to long-term urban sustainability, social inclusivity, and overall quality of life.